FLASH CARD MEDIA; BELAJAR SAMBIL BERMAIN DALAM MEMPERMUDAH MENGENAL KATA DI MADRASAH - Muhammad Thoiful Abrar; Listrianti, Feriska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Vocabulary learning in early childhood plays an important role in their language and cognitive development. One effective method to improve children's understanding and motivation to learn is the use of flashcard media. This study aims to analyze the application of flashcards in learning in madrasahs as an effort to facilitate word recognition in students. The research method used is descriptive analysis with a qualitative approach, involving observation, interviews, and documentation. The results of the study showed that the use of flashcards helps improve students' memory, makes learning more interactive, and increases their learning motivation. In addition, this media allows flexible learning according to each student's learning style. Although there are challenges in implementation, such as material preparation that takes time, flashcards have proven to be an innovative solution in improving children's vocabulary skills in madrasahs. Therefore, the use of flashcards is recommended as an effective and interesting learning media for early childhood.